Effects of propofol on wound closure and barrier function of cultured endothelial cells: An in vitro experimental study. Issue 3 (March 2018) - Zitta, Karina; Hummitzsch, Lars; Broch, Ole; Gruenewald, Matthias; Ohnesorge, Henning; Parczany, Kerstin; Steinfath, Markus; Albrecht, Martin
Abstract : BACKGROUND: Propofol is widely used in routine clinical practice for the induction and maintenance of anaesthesia. Although propofol is regarded as a well tolerated anaesthetic, its effect on intact or damaged endothelial cells has not yet been elucidated. OBJECTIVE: The aim of this study was to investigate the effects of different concentrations of propofol on cell damage, metabolic activity, barrier function and wound healing capacity of human endothelial cells. DESIGN: An in vitro investigation. SETTING: Research Laboratory of the Department of Anaesthesiology and Intensive Care Medicine, University Hospital Schleswig-Holstein, Kiel, Germany. MATERIALS: In vitro cultures of primary human umbilical vein endothelial cells (HUVECs). INTERVENTIONS: Intact HUVEC or wounded HUVEC monolayers were incubated with or without different concentrations of propofol (10, 30 and 100 μmol l -1 ). MAIN OUTCOME MEASURES: Cell damage, metabolic activity, monolayer permeability, wound healing capacity, protein phosphorylation. RESULTS: Propofol did not alter the morphology, induce cell damage or influence metabolic activity of intact HUVEC cells. Permeability of a HUVEC monolayer was increased by propofol 100 μmol l -1 ( P < 0.05). Wound closure was inhibited by the addition of propofol 30 and 100 μmol l -1 ( P < 0.05 and P < 0.01). This effect was associated with increased phosphorylation of extracellular signal regulated kinases (Erk) 1/2 (30 and 100 μmol l -1 ; both P < 0.05) and decreased phosphorylation of Rho kinase (Rock) (100 μmol l -1 ; P < 0.05). CONCLUSION: Propofol does not damage intact endothelial cells, but increases permeability of an endothelial cell monolayer at high concentrations and inhibits wound closure in vitro. Further experimental and clinical in vivo research should be performed to clarify the influence of propofol on endothelial wound healing.